Limit analysis of thin-wall metal frames taking into account their foundations rigidity = Analiza nośności granicznej ram cienkościennych przy uwzględnieniu sztywności ich fundamentów - Alawdin, Piotr; Petrusevich, Viktoryia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper, the mathematical model of shakedown optimization problem of limit analysis for the thin-wall metal frames under variable quasi-static loads is presented. Authors assume the elastic-plastic flexural buckling in one plane without lateral torsional buckling behavior of members on conditions of the ideal elastic-plastic behaviour of the frames materials.
Keywords: shakedown analysis; thin-wall metal frames; foundations rigidity; mathematical model; nośność graniczna; ramy cienkościenne; sztywność fundamentów; model matematyczny